2016
DOI: 10.1111/pim.12305
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Necrosis Factor‐alpha (TNF‐α) and its soluble receptor type 1 (sTNFR I) in human active and healed leishmaniases

Abstract: The role of tumour necrosis factor-alpha (TNF-α) is not fully understood in human leishmaniasis. We analysed the alterations in the levels of TNF-α, soluble TNF receptor type 1 (sTNFR I), IL-17 and IL-22 productions in active and healed leishmaniases. Blood samples were collected from volunteers with active cutaneous leishmaniasis (ACL), the same subjects after lesion healing (healed CL = HCL), volunteers with active visceral leishmaniasis (AVL), healed VL (HVL) and healthy controls. Levels of cytokines were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 28 publications
1
22
1
Order By: Relevance
“…Collectively, it seems that IL‐17a has a dual permissive and protective role during the Leishmania infection. In fact, regulated levels of IL‐17a yield protective immunity against leishmaniasis, whereas extreme levels of this pro‐inflammatory cytokine associate with persistent tissue damage .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Collectively, it seems that IL‐17a has a dual permissive and protective role during the Leishmania infection. In fact, regulated levels of IL‐17a yield protective immunity against leishmaniasis, whereas extreme levels of this pro‐inflammatory cytokine associate with persistent tissue damage .…”
Section: Discussionsupporting
confidence: 93%
“…Leishmanicidal activity of IFN‐ γ is, however, supported by IL‐17a cytokine produced by TH17 cells. These cells protect mucosal and skin tissue of Leishmania ‐infected mice through neutrophil and monocyte recruitment .…”
Section: Introductionmentioning
confidence: 93%
“…Duthie and coworkers [50] have shown that both IL-10 and IL-17 cytokines are elevated in the serum of active VL patients, reverting to baseline levels with standard antimonial treatments. AHR activation has also been shown to inhibit inflammation through upregulation of IL-22 [52], another cytokine that has been shown to be significantly higher in Leishmania antigen stimulated peripheral blood mononuclear cells from active VL cases compared to treated cases [53]. AHR activation during VL may underpin the complex regulation of pro- and anti-inflammatory responses during disease pathogenesis and during response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Europe (KAYE and SCOTT, 2011;NATEGHI ROSTAMI et al, 2016). Though, more than 90% of potentially fatal infections occur in just six regions: Brazil, Ethiopia, Sudan, South Sudan, India and Bangladesh (PIGOTT et al, 2014).…”
Section: Leishmaniases: Life Cycle Clinical Manifestations and Chemomentioning
confidence: 99%
“…Europe (KAYE and SCOTT, 2011;NATEGHI ROSTAMI et al, 2016). The intracellular localization of leishmaniases parasites hinders access of the chemotherapy to the site of action.…”
Section: Introductionmentioning
confidence: 99%